Supply Chain Management: Survey Consumer Preferences and Market Potential (Study Literature Review) - Candra Susanto, Primadi; Saribanon, Euis; Pahala, Yosi; Liana, Esti; Purwoko, Harry (International Journal of Advanced Multidisciplinary, 2024)
The supply chain management article: survey of consumer preferences and market potential is a scientific literature review article within the scope of operational management science. This article aims to create a hypothesis regarding the relationship between factors, which can subsequently be utilized for future research in the field of human resource management. Descriptive qualitative research methodology was employed in this study. The data utilized in this study was derived from prior research that remains pertinent to the current investigation. The data was gathered from reputable academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sinta journals. The findings of this study are as follows: 1) Consumer preference surveys play a role in supply chain management: Surveys offer significant insights into consumer preferences, wants, and expectations pertaining to a specific product or service. These insights serve as the foundation for organizations in formulating marketing strategies, developing products, and managing inventory. By gaining a comprehensive grasp of consumer preferences, organizations have the potential to enhance customer happiness, streamline their supply chains, and attain a competitive edge in marketplaces that are becoming progressively intricate and dynamic; and 2) Market potential plays a role in supply chain management: market potential offers a comprehensive overview of the current market size, potential for growth, and consumer patterns in a specific region or demography. This data enables organizations to develop supply chain strategies that are characterized by enhanced efficiency and adaptability in response to dynamic market needs. Through a comprehensive comprehension of market potential, organizations are able to effectively identify prospective market segments, formulate suitable expansion strategies, and adapt their supply chain approaches in order to maximize profitability and foster corporate expansion.